Metodologi Pendidikan Dalam Hadist Pada Pendidikan Anak Usia Dini - tika, Dina Rohma; Yusra Arsila, Yusra Arsila; Moh Irwansyah, Moh Irwansyah (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
Education has the biggest role in the development of a nation’s civilization. As for efforts to realize educational goals, it must start from the formation of character in early childhood. Early childhood is the right time to lay the foundations for the formation of a complete personality. At an early age, children need to be educated as well as possible according to methods adapted to their situations and conditions. If early childhood is accustomed nd educated with good things, then he will grow and develop well and will again happiness and avoid misery both in this world an in the hereafter. In the Hadith, the messenger of Allah has given many examples of life lessons including the issue of education on how the Prophet thaught his friends, including his friends who were still at an early age. In providing teaching, the Prophet Muhammad always chose methods that were effective and efficient, easy to understand and understand and easy to digest according to the abilities and abilities of the students.  In this study, using the method of library research. Likewise with the data collection techniques used in this study, namely library research. While the data analysis technique used in this study is the method of content analysis. The educational methodology in hadith in early childhood is: Exemplary method, Dialogue or Discussion method, Story method, Demonstration method, Giving Rewards, Giving punishmant.Keywords: Methodology, Education, Early Childhoo